'User-Home relationship' regarding user experience of smart home products. (2nd January 2022) - Sadikoglu-Asan, Hatice
ABSTRACT: Technological developments in recent years have radically advanced the design of smart home products. With the help of artificial intelligence, the interaction between user and product has been raised to a new level. While AI has been changing the type of interaction, the relationships between user, product and home have gained importance to provide useful and meaningful outputs for smart home systems. This paper proposes a new approach by focusing on a specific relationship. The aim of the study is to explore the relationship between the user and the home to obtain insight into improving the user experience quality. The research explores specific characteristics such as home-occupancy status, home type and number of members of a household. This study consists of a literature review on the concept of smart home and a field study. The field study was conducted with 48 participants in the Bay Area, San Francisco. Following this, multiple-choice questionnaires and semi-structured interviews were conducted. With the findings of the study, the impact of the user-home relationship on the user experience of smart home products is discussed. We propose that this relationship should be taken into consideration as a new dynamic dimension for developing user experience strategies.